2022
DOI: 10.20517/2394-5079.2022.13
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic fibrosis and incidence of HCC following direct-acting antiviral treatment of F3 chronic hepatitis c patients: a prospective observational study

Abstract: Aim: Studies of clinical outcomes in chronic hepatitis C (CHC) patients with pretreatment advanced liver fibrosis (F3) after sustained virologic response (SVR) are scarce, and most studies are of small cohorts and retrospective in nature. Our aim was to assess the clinical outcomes following direct acting antiviral (DAA) treatment among hepatitis C F3 patients after SVR. Methods: This study included 1517 chronic hepatitis C patients with F3 fibrosis receiving DAAs in the out-patient clinics at the Egyptian Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Liver fibrosis regression is an important variable to study as it has been shown to decrease complications, such as HCC, and the need for transplantation. Several studies reported a reduction in the rate of HCC following DAA treatment as a result of liver fibrosis regression [ 7 , 9 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liver fibrosis regression is an important variable to study as it has been shown to decrease complications, such as HCC, and the need for transplantation. Several studies reported a reduction in the rate of HCC following DAA treatment as a result of liver fibrosis regression [ 7 , 9 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of HCV infection is variable and depends on various factors; hepatic injury can range from minimal necroinflammatory changes to extensive liver fibrosis and cirrhosis development and increases the risk of hepatocellular carcinoma (HCC) development. The updated literature has shown improvements in liver fibrosis (LF) after treatment with DAAs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 96 weeks after successful DAA treatment, 17% of patients had progressive hepatic fibrosis [ 9 ]. In another observational study, the progression of liver fibrosis occurred in 12.5% of patients achieving SVR post-DAA therapy [ 10 ]. Notably, the incidence rate of HCC was the highest among patients with fibrosis progression (6.17/100 patient-years) compared to patients with stable fibrosis (1.09/100 patient-years) and those with fibrosis regression (0.75/100 patient-years) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another observational study, the progression of liver fibrosis occurred in 12.5% of patients achieving SVR post-DAA therapy [ 10 ]. Notably, the incidence rate of HCC was the highest among patients with fibrosis progression (6.17/100 patient-years) compared to patients with stable fibrosis (1.09/100 patient-years) and those with fibrosis regression (0.75/100 patient-years) [ 10 ]. These findings supported an observation in a previous cohort study showing that patients with progressive liver fibrosis after SVR had a significantly higher rate of HCC development than those with fibrosis regression or stability (33% vs. 4% at 5 years, p < 0.001) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%